THE INFLUENCE OF SUPERVISION AND SOCIALIZATION STRATEGIES OF BAWASLU MEDAN CITY ON PUBLIC PARTICIPATION IN THE 2024 ELECTION - Rencina; Risnawati Sianturi; Ida Ela R Limbong; Nalom Siagian; Artha Lumban Tobing (Pena Cendekia Insani, 2026)
This study examined the influence of the supervisory strategy and socialization strategy of the Election Supervisory Body of Medan City on community participation in the 2024 election. The problem addressed was the declining voter participation rate and the gap between implemented electoral supervision efforts and actual public involvement. A quantitative approach was employed using survey data collected from community respondents. The supervisory strategy was measured through preventive actions, law enforcement, and participatory monitoring, while the socialization strategy was assessed through information dissemination, public education, and communication media utilization. The findings indicated that both supervisory and socialization strategies significantly affected community participation. The socialization strategy showed a stronger influence because effective dissemination of electoral information improved public awareness and motivation to vote. The study concluded that strengthening communication-based outreach and community-based monitoring enhanced democratic participation and supported the realization of fair and credible elections.